Heterojunctions fabricated by surface activated bonding–dependence of their nanostructural and electrical characteristics on thermal process. (1st December 2022) - Shigekawa, Naoteru; Liang, Jianbo; Ohno, Yutaka
Abstract: Recent achievements in the research of heterojunctions fabricated using surface activated bonding (SAB), one of the practically useful direct wafer bonding technologies, are discussed. The response of bonding interfaces to post-bonding annealing is focused. These junctions reveal high thermal tolerance (1000 °C in the case of junctions made of widegap materials) despite differences in coefficients of thermal expansion between bonded materials. Defect layers with several nm thickness formed by the surface activation process at the as-bonded interfaces get faint and their electrical and mechanical properties are improved by annealing. These results show that as-bonded interfaces are in a metastable state, and novel functional devices are likely to be realized by applying wafer processing steps to SAB-based junctions. Characteristics of III–V//Si multijunction solar cells, GaN-on-diamond high electron mobility transistors, and metal-foil based low-loss interconnects that are fabricated by processing SAB-based junctions are described, and future prospects are presented.